Reported reasons for initiating drug use among drug-dependent adolescents and youths in Yunnan, China. - Yang, Lijun; Li, Jianghong; Yiping, Zhang; Wendong, Zhang; Fuqiang, Dai; Ren, Zhouyang; Maycock, Bruce (The American journal of drug and alcohol abuse, 2009)
As an entry point for illicit drug trafficking, Yunnan was hit hard by the twin epidemics of drug abuse and HIV/AIDS. There are no empirical studies regarding the reasons for initiation of drug use in Yunnan.
Keywords: Adolescent; Adolescent Behavior; Age of Onset; China; Demography; Drug Users; Exploratory Behavior; Female; Health Knowledge, Attitudes, Practice; Humans; Male; Substance-Related Disorders; Young Adult